Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.3390/en12132564
|View full text |Cite
|
Sign up to set email alerts
|

A Super-Twisting Sliding-Mode Stator Flux Observer for Sensorless Direct Torque and Flux Control of IPMSM

Abstract: The scheme based on direct torque and flux control (DTFC) as well as active flux is a good choice for the interior permanent magnet synchronous motor (IPMSM) sensorless control. The precision of the stator flux observation is essential for this scheme. However, the performance of traditional observers like pure integrator and the low-pass filter (LPF) is severely deteriorated by disturbances, especially dc offset. Recently, a sliding-mode stator flux observer (SMFO) was proposed to reduce the dc offset in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…The active flux based sensorless control method is applied. The active flux Ψ AF is defined as a hypothetical flux, which multiplied by the instantaneous q-axis current i q produces the measured instantaneous electro-magnetic torque t e [32][33][34][35]. Consequently, the effects which are neglected in the PMSM model are thus considered by employment of Ψ AF .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The active flux based sensorless control method is applied. The active flux Ψ AF is defined as a hypothetical flux, which multiplied by the instantaneous q-axis current i q produces the measured instantaneous electro-magnetic torque t e [32][33][34][35]. Consequently, the effects which are neglected in the PMSM model are thus considered by employment of Ψ AF .…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, in this work the ME characteristics are implemented in sensorless control for the first time and presented in Section 4. There the rotor speed and position are determined by nonlinear phase-locked loop (PLL) observer [9,31], whose inputs are calculated by the modified active flux method [32][33][34][35]. It is shown that the drive efficiency can be improved when ME characteristics are used to generate the d-and q-axis current references, which is true for the sensorless control as well as for the control realization with position sensor.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in (18), due to the saliency L d ≠ L q of IPMSMs, its reluctance torque can be utilised to maximise the electrical torque with the same stator current. In addition, simple i d = 0 control will reduce the efficiency of IPMSMs.…”
Section: Active Flux-based Flux Adaption Dtfcmentioning
confidence: 99%
“…Boldea et al [17] describe the concept of active flux and the active flux is always utilised to realise the sensorless control of IPMSM. In [18,19], the active flux is observed by an SMO, and then the rotor position information can be obtained easily. In [20], a high-frequency injection method which makes up for the low signal noise ratio of active flux at low speed is combined with the active flux to realise sensorless control in full speed domain.…”
Section: Introductionmentioning
confidence: 99%
“…The drive system of interior permanent magnet synchronous motors (IPMSMs) [1,2] based on two-level voltage source inverters (2L-VSIs) [3,4] has become one of the mainstream speed control schemes for electric vehicles (EVs) due to advantages, such as high efficiency, excellent speed regulation performance, and high power density. In order to improve the security of EVs, the functional safety of the drive system has gradually become one of the research hotspots.…”
Section: Introductionmentioning
confidence: 99%